Sentinel HSV Infection Revealing Systemic Lupus Erythematosus and Antiphospholipid Syndrome in a Chronically Ill Adolescent Female:: A Case Report - Puno, John Paulo; Carvajal, Carien; Caringal, Christine; Reyes-Rodolfo, Jacqueline; Mabulac, Marichu; Salonga-Quimpo, Rhea Angela (Philippine Journal of Allergy, Asthma and Immunology, 2025)
Childhood-onset systemic lupus erythematosus (cSLE) is a severe autoimmune disorder with diverse multisystem manifestations; neuropsychiatric involvement is an uncommon initial feature. Herpes simplex virus (HSV) encephalitis, although rare, is a potentially life-threatening infection that primarily affects immunocompromised individuals, including those with SLE. Cases where HSV encephalitis precedes SLE diagnosis are exceedingly rare. We present a 14-year-old Filipino female with autoimmune thyroiditis who developed acute behavioral changes after a mild febrile illness. Cranial MRI revealed an acute right frontotemporoparietal infarct; laboratory workup showed bicytopenia and nephrotic-range proteinuria. Positive HSV-1 IgG supported a diagnosis of HSV encephalitis, and empiric acyclovir was initiated. Strongly positive antinuclear antibodies met the entry criterion of the 2019 European League Against Rheumatism /American College of Rheumatology (EULAR/ACR) criteria, with the mucocutaneous, hematologic, and renal domains fulfilled. Her course was complicated by severe hypertension, Class III lupus nephritis, and persistent lupus anticoagulant positivity with cerebral infarction, confirming secondary antiphospholipid antibody syndrome. This case illustrates the layered pathology of infection, inflammation, and thrombosis, where an infectious trigger unmasked an autoimmune process and vascular complications. The interplay between HSV neurotropism and immune dysregulation may have predisposed her to neuroinflammation and systemic autoimmunity. Early multidisciplinary intervention was pivotal to recovery. Further studies are needed to clarify viral-autoimmune interactions in pediatric SLE.